Interaction between sodium vapor and reactor wall during biomass combustion and its influence on measurement of particulate matter emission - Gao, X.; Chen, Y.; Sheng, C.; Wu, Hongwei (2016)
A mallee bark (75–150 μm) was washed with 0.1 M sulfuric acid, followed by preparing a Na-exchanged bark via ion-exchange process and a NaCl-loaded bark via wet impregnation. The Na-exchanged bark and the NaCl-loaded bark were then combusted at 1300 °C in air using a novel laboratory-scale drop-tube furnace (DTF) which consists of an inner reactor tube cascaded into an outer heating tube. The results demonstrate the retention of water-soluble Na in the reactor tube after the combustion of the Na-exchanged bark and the NaCl-loaded bark, confirming the interaction between Na vapor and the reactor tube during biomass combustion. Such interaction is dependent on the occurrence forms of Na (or the availability of chlorine, Cl) in the combustion feedstock. In the absence of Cl (i.e., the Na-exchanged bark combustion), the amount of water-soluble Na retained in the reactor tube is ∼4 times higher than that in the presence of Cl (i.e., the NaCl-loaded bark combustion). The data provide new insights into the roles of Cl in the emission of Na in the particulate matter (PM) with aerodynamic diameters of <10 μm (PM10). The retained water-soluble Na is instable and can be released again during the combustion of Cl-surplus polyvinyl chloride (PVC) particles, contributing to PM10 emission and thereby distorting the measurement of its emission.